Flexible thin-film thermal sensor for estimating thermal transport properties designed for biomaterial applications - Takahiro Okabe; Ayumi Shiroto; Yuto Hiyama; Katsuhisa Taguchi (Scientific Reports)
Abstract This study develops a flexible thin-film thermal sensor for estimating the key thermal transport properties of biomaterials, namely thermal conductivity, volumetric heat capacity, and thermal contact resistance. The sensor included a circular thin-film heater and three thin-film NTC thermistors mounted on a polyimide substrate, enabling simultaneous temperature measurements in regions of heat concentration and diffusion. These measurements were used in an inverse analysis based on a three-dimensional heat conduction model. To account for the variability in contact conditions, the thermal contact resistance between the sensor and sample surface was included as an unknown parameter. A trust-region reflective algorithm was used for robust minimization of the objective function. Validation was conducted using standard materials with known properties and porcine fat as a biological sample. The results showed excellent agreement between the measured and simulated temperature profiles. The estimated values for thermal conductivity and volumetric heat capacity closely matched reference values, and the thermal contact resistance was consistently in the order of 10−4 (m2 K)/W, likely owing to surface roughness. These results demonstrate the effectiveness of the proposed sensor and the inverse analysis method in enabling noninvasive and accurate evaluation of thermal transport properties in soft biological tissues.